Question: "\\frac {dr}{d\\theta}+rsec(\\theta)=cos(\\theta)"
Solution:
Substituting "r=uv" , "r'=u'v+uv'" : (1)
"u'v+uv'+sec(\\theta)uv=cos(\\theta)"
"u'v+u(v'+sec(\\theta)v)=cos(\\theta)" (2)
Setting the part inside () to 0 and separating variables:
"v'+sec(\\theta)v=0"
"\\frac {dv}{d\\theta}=-sec(\\theta)v"
"\\int \\frac {dv}{d\\theta}=-\\int sec(\\theta)"
"ln(v)=-ln(sec(\\theta)+tan(\\theta)) + ln(k)"
"ln(v)=ln(\\frac k {sec(\\theta)+tan(\\theta)})"
"v=\\frac k {sec(\\theta)+tan(\\theta)}"
Putting "v" from (3) into equation (2):
"u'\\frac k {sec(\\theta)+tan(\\theta)}=cos(\\theta)"
Using trigonometric identities "sec(\\theta)=\\frac 1 {cos(\\theta)}" , "tan(\\theta)=\\frac {sin(\\theta)}{cos(\\theta)}" :
"du=\\frac 1k cos(\\theta)(sec(\\theta)+tan(\\theta))d\\theta=\\frac 1k (1+sin(\\theta))d\\theta"
"u=\\frac 1k \\int (1+sin(\\theta))d\\theta = \\frac 1k (\\theta-cos(\\theta)+C)"
Finding r from (1):
"r=uv=\\frac {\\theta-cos(\\theta)+C}{sec(\\theta)+tan(\\theta)}"
Answer: "r=\\frac {\\theta-cos(\\theta)+C}{sec(\\theta)+tan(\\theta)}"
Comments
Leave a comment